Public policies and housing vulnerabilities in face of the COVID-19 pandemic - Silva, Maria das Graças; Gallardo, Amarilis Lucia Castelli Figueiredo (National Journal of City Management, 2020)
In the history of mankind there have been episodes marked by the spread of diseases, victimizing populations on a global scale. Despite the advancement of time and technologies, situations of uncertainty and insecurity are repeated, problems of management and control of the pandemic situation, associated with the race to search for its causes and to obtain its cure. The pandemic may end, but the vulnerability and health, well-being and housing problems will persist if there are no advances in governance and management of public and of sectors policies, involving the management of services and urban infrastructure. Added to this is the delay in carrying out national plans, projects and programs, as well as the international agreements established to promote quality of life. The aim of the present study is to analyze aspects of public policies, socioeconomic and housing vulnerabilities considering the context of the COVID-19 pandemic, by means of a qualitative research of exploratory character.